Phenolic profiles and chemical- or cell-based antioxidant activities of four star fruit (Averrhoa carambola) cultivars. Issue 93 (21st September 2016) - Pang, Daorui; You, Lijun; Li, Tong; Zhou, Lin; Sun-Waterhouse, Dongxiao; Liu, Rui Hai
Abstract : Phenolic profiles and chemical- or cell-based antioxidant activities of different Averrhoa carambola cultivars cultivated in South China. Abstract : The objectives of this study were to investigate the phytochemical profiles and antioxidant activities of four cultivars of star fruit ( Averrhoa carambola ). The free, bound and total phenolic contents of the four cultivars were 162.5–286.8, 6.4–19.7, and 174.5–293.1 mg gallic acid equivalents per 100 g fresh weight (FW), respectively. The free, bound and total flavonoid contents were 100.7–234.0, 1.1–7.8, and 104.4–235.1 mg catechin equivalents per 100 g FW, respectively. The cellular antioxidant activity (CAA) values with or without a phosphate buffered saline wash protocol ranged from 25.80 to 63.29 and from 32.41 to 68.96 μmol quercetin equivalents per 100 g FW, respectively. The Taiguo cultivar had the highest phytochemical content and antioxidant activity among the four cultivars tested. High performance liquid chromatography analysis revealed the presence of gallic acid, syringic acid, p -coumaric acid, epicatechin, isoquercetin and procyanidin B2 in Averrhoa carambola . The type of cultivars influenced the phytochemical profile and extractability, antioxidant activity, and ultimately health-promoting potential of star fruit.